Pessoalidade e identidade na doença de Alzheimer: interpretando a lei para inclusão e proteção da pessoa com demência - David Salim Santos Hosni (2017)
Alzheimers disease is a neurodegenerative pathology affecting cognitive domains including episodic memory, semantic memory, visuospatial abilities, and executive functioning. Other symptoms includes anosognosia, attention deficits, changes in mood and personality traits, and other psychiatric symptoms. Beyond this medical approach, some have tried to grasp the disease from a different perspective, trying to characterize the whole process as a disease affecting personhood, in which the organic symptoms are just part of a bigger picture of a personhood pathology. From this perspective, we attempt to investigate Stanciolis concept of personhood and Parfits unimportance of identity as a theoretical background to the judgment of our ethical obligations to persons with dementia. The practical analysis was made from selected vignettes, which gave us the opportunity to find out the situations that most affect the personhood of the person with dementia. This background made possible for us to analyze the legislation concerning the inclusion and protection of persons with dementia and to claim that the efficacy of the Persons with Disability Statute (Lei n. 13.146/2015) and of the legislation about substitute decision making in the Civil Procedure Code (Lei n. 13.105/2015) are dependent upon an adequate apprehension of a functional disability concept not grounded on conditions of high cognitive abilities or discernment.